Effect of Saccharomyces cerevisiae and Tea Extract on Root Nodulation by Rhizobium spp. and Growth Parameters of Vicia faba L. - Khlaf, Waser Saad; Abbas, Haneen Faddil; Shakir, Hussam Nafea (American Journal of Biology and Natural Sciences, 2025)
The experiment was conducted at the Field Crops Department Research Station, College of Agriculture, Samarra University, during the winter agricultural season 2024/2025, with implementation beginning on 12 November 2024. The experiment included three experimental treatments: yeast extract (R3), tea extract (R2), and the control treatment (R1). A local variety of broad bean was cultivated. This experiment was designed as a simple randomised complete block design (RCBD), with three replicates, resulting in a total of nine experimental units each unit contained four plants. This study aimed to evaluate the effects of yeast and tea extracts as organic fertilisers on the growth and anatomical characteristics of fava beans. Results showed that both biological treatments improved plant morphology compared to the control, with the tea extract yielding the highest stem length, number of leaves, and number of branches. The yeast extract, on the other hand, outperformed the control in the number of nodes. Anatomical analyses further revealed that both treatments increased stomatal number and index in the leaf epidermis, particularly the tea extract group. These improvements are attributed to the natural growth regulators and nutrients present in the extracts. Overall, the results confirm the potential of organic fertilisation in improving plant growth and leaf anatomy. The study recommends the use yeast and tea extracts as natural alternatives to synthetic fertilisers.